Knowledge, attitude and practices among the inhabitants of Lahore, Pakistan towards the COVID-19 pandemic: an immediate online based cross-sectional survey while people are under the lockdown. - Ashiq, Kanwal; Ashiq, Sana; Bajwa, Mayyda Asif; Tanveer, Samreen; Qayyum, Mehwish (Bangladesh Journal of Medical Science, 2020)
Background: COVID-19 is an emerging infectious disease and has reached a status of global health emergency. It is widespread in Pakistan causing morbidity and mortality amongst masses. Objectives: Undertaken study aims at investigating knowledge, attitude and practices of the people residing in Lahore, Pakistan whilst the global crisis with sparse data available previously. Methodology: Following lockdown announcement, an immediate online cross sectional study was conducted from the 31st March to 6 April 2020. Data was analyzed by using SPSS IBM version 22. 00. Results: A total of 316 responses were received. Our study has shown that people 95.80% were well familiar with COVID-19, informed via news channels 46.2%. 91.7% believed the virus is contagious, 95.8% reported that the virus is spread by the respiratory droplets, 89.2% believed that all ages are at risk while 62.3% believed it risky for geriatrics only. 60.4% believed in its prevention with 91.7% respondents agreeably quarantined themselves while 6.6% didn’t. 99.7% participants were aware of social/physical distancing and 75.6% found it affecting mental health i.e. cause anxiety, depression etc. 59.2% of respondents were optimistic expecting it to end soon while 32.3% were uncertain. 49.1% said they have diagnostic facility and 89.6% acknowledged efforts of researchers/healthcare providers (doctors, pharmacist, nurses, allied health professionals and paramedical staff) for the society. 94.3% believed that there is need of awareness regarding COVID-19. Conclusion: An ever increasing need of awareness amongst the local population regarding COVID-19 is needed. It will lend hands in preventing spread of COVID-19 with minimal secondary transmission. It is recommended that extensive survey studies are required that can provide supportive data in developing and implementing public health policies regarding COVID-19 pandemic. It would further control and arrest the spread of COVID-19 in country. Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 69-S 76